Control de cuentas por cobrar en los periodos 2021-2022 de la empresa Servicios Eléctricos y Ferretería Electroferro S.A. del cantón Ventanas. - Salavarria Barrionuevo, Mayte Arleth (2024)
The case study carried out in the Electrical Services and Hardware company Electroferro S.A. was based on the exploration of accounts receivable management during the 2021-2022 fiscal periods, revealing how internal dynamics and financial strategies influence the liquidity and economic stability of the company. The issue highlighted the importance of efficiently managing accounts receivable, a practice that can determine a company's long-term competitiveness and viability in today's business environment. This project is justified by the need to understand the implications of ineffective management of accounts receivable, the research sought to offer a detailed understanding of how credit policy and collection procedures impact the liquidity and solvency of the company, with the ultimate goal of providing recommendations to optimize these practices. Focusing on specific objectives that included the identification of accounts receivable items, the vertical and horizontal analysis of financial statements, and the evaluation of financial performance using indicators, the methodology adopted a qualitative and quantitative approach. The financial statements provided by the company were analyzed, using financial analysis techniques to evaluate the turnover of accounts receivable and the average payment period, which allowed a deep interpretation of the current financial situation and its evolution over time.